Advances in WRKY regulation of immune responses in medicinal plants - Zhong, Xinying; Chen, Nana; Li, Hongwei; Wang, Yaxuan; Guo, Ziyi; Shi, Guiyuan; Zhan, Xingkai; Li, Lin (Frontiers in Plant Science, 2025)
Medicinal plants serve as a crucial source of traditional Chinese medicine and have garnered considerable attention due to their unique bioactive compounds and notable pharmacological properties. However, during natural growth, these plants are frequently susceptible to infection by various pathogenic microorganisms, pests and nematodes, leading to reduced yields and inconsistent accumulation of medicinal compounds, thereby significantly limiting their resource development and utilization. WRKY transcription factors (TFs) are central regulators of plant immunity that integrate pathogen-perception signals, coordinate signaling pathways, and transcriptionally control defense-gene expression. This review provides a systematic synthesis of current knowledge on the regulatory mechanisms of WRKY TFs in the immune responses of medicinal plants. Emphasis is placed on their roles in cellular metabolic regulation, activation of Mitogen-Activated Protein Kinase (MAPK) signaling pathways, integration of phytohormone signaling, and the biosynthesis of secondary metabolites. In addition, we highlight that WRKY TFs orchestrate immune responses at multiple levels through epigenetic mechanisms, including DNA methylation and histone modifications. Furthermore, it is proposed that transgenic approaches and Cut-Dip-Budding (CDB)-mediated transformation be integrated with gene editing technologies such as Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR), in conjunction with artificial intelligence (AI)-assisted identification of key regulatory elements. This integrated strategy offers novel insights and theoretical support for establishing efficient immune regulatory networks and breeding disease-resistant medicinal plant varieties.